Relational model vs. dimensional model-further experimentation on understandability of the two schemas - Mat Yusof, Sharmila; Sidi, Fatimah (2014)
Data warehouse (DW) has been commonly accepted as a solution to support organization’s decision support. Despite technical aspects of DW implementation, one of the most important tasks that need to be considered is its data modeling. Data modeling is important as it deals with structuring the data so that users can easily access for decision support process. The two predominant data models in data warehouse project are dimensional model (i.e. Star Schema Diagram (SSD)) and relational model (i.e. Entity-Relationship Diagram (ERD)). The decision whether to build a data warehouse using either model has created controversy among practitioners. Semantic network theory support that SSD is better than ERD in terms of its understanding measures. However, previous studies have produced conflicting result regarding the support and claim. Thus, the objective of this study is to further explore whether one schema is better than another in terms of its understandability. This study aims to design and conduct an experiment that test the understandability of the SSD and ERD with schema complexity factor.